114k views
3 votes
7. Write an equation that results when f(x) = 5^x has been transformed by:a. Shifted to the left 2 and up 3b. Shifted right 3 and down 1

User Nemmy
by
6.1k points

1 Answer

6 votes

Answer:


\begin{gathered} (a)g(x)=5^(x+2)+3 \\ (b)g(x)=5^(x-3)-1 \end{gathered}

Step-by-step explanation:

Given the parent function f(x) defined below:


f\mleft(x\mright)=5^x

Part A

When f(x) is shifted to the left 2 units:


f(x+2)=5^(x+2)

Next, shifted up by 3 units:


f(x+2)+3=5^(x+2)+3

The result is:


g(x)=5^(x+2)+3

Part B

When f(x) is shifted to the right 3 units:


f(x-3)=5^(x-3)

Next, shifted down by 1 unit:


f(x-3)-1=5^(x-3)-1

The result is:


g(x)=5^(x-3)-1

User Carlos Blanco
by
6.6k points